Assessment of Serum IL-2 and Immunohistochemistry Detection of IL-2 in Induced Hypothyroidism of Male Rats - Abbas Abed Sharhan (Journal of Global Pharma Technology, 2018)
This study was conducted to demonstrate the role of methanolic extract from Ficuscarica leaves in the treatment of hypothyroidism disease which induced in male rats by carbimazole drug. Forty male rats were divided into five groups, eight for each. group I selected as a negative control which primed orally with normal saline alone, group II served as a positive control and treated by carbimazole anti-thyroid drug for six weeks ,while group III was treated by plant extract ( 500 mg /kg, bw) for six weeks ,whereas the fourth group IV was treated by carbimazole drug (5 mg) for six weeks to induce hypothyroidism and then treated by plant extract ( 500 mg /kg , bw) for six weeks too. Finally the fifth V group was treated by thyroxin drug (100 mg) for six week instead of plant extract.The results showed that a non- significant difference (P< 0.05) in the level of IL-2 of the fourth group when compared with the first group , while the results revealed a significant increase when compared with the second group ,whereas a significance decrease when compared with the third and fifth groups. The immunohistochemical sections of rats thyroid gland in the first , second and third groups revealed that weak expression of IL-2 immunopositive cells (brown cytoplasmic deposits) in thyroid sections, while rats thyroid gland in the fourth group and fifth groups revealed that a moderate expression of IL-2 immunopositive cells. In conclusion it is possible to use methanolic extract of Ficuscarica leaves in the regulation of immune response in hypothyroidism disease may due to the presence of phytochemical components that enhance the cellular immune response by increase the IL-2 production. Keywords: Hypothyroidism, Carbimazole IL-2, Immunohistochemistry, Ficuscarica, phytochemical components.